Larval density mediates knockdown resistance to pyrethroid insecticides in adult Aedes aegypti - Grossman, Marissa K.; Uc Puc, Valentín; Flores, Adriana E.; Manrique Saide, Pablo C.; Vazquez Prokopec, Gonzalo M. (Biomed Central, 2018)
Abstract Background: Understanding mechanisms driving insecticide resistance in vector populations remains a public health priority. To date, most research has focused on the genetic mechanisms underpinning resistance, yet it is unclear what role environmental drivers may play in shaping phenotypic expression. One of the key environmental drivers of Aedes aegypti mosquito population dynamics is resource-driven intraspecific competition at the larval stage. We experimentally investigated the role of density-dependent larval competition in mediating resistance evolution in Ae. aegypti, using knockdown resistance (kdr) as a marker of genotypic resistance and CDC bottle bioassays to determine phenotype. We reared first-instar larvae from susceptible and pyrethroid-resistant field-derived populations of Ae. aegypti at high and low density and measured the resulting phenotypic resistance and population kdr allele frequencies. Results: At low density, only 48.2% of the resistant population was knocked down, yet at high density, the population was no longer phenotypically resistant - 93% were knocked down when exposed to permethrin, which is considered susceptible according to WHO guidelines. Furthermore, the frequency of the C1534 kdr allele in the resistant population at high density decreased from 0.98 ± 0.04 to 0.69 ± 0.04 in only one generation of selection. Conclusions: Our results indicate that larval conditions, specifically density, can impact both phenotype and genotype of pyrethroid-resistant populations. Furthermore, phenotypic susceptibility to pyrethroids may be re-established in a resistant population through a gene x environment interaction, a finding that can lead to the development of novel resistance management strategies that capitalize on density-induced costs. Keywords: Pyrethroid resistance, Aedes aegypti, Intraspecific competition, kdr